Evaluation of Inflammatory Serum Cytokines after Treatment with the Consciousness Energy Healing Based Proprietary Test Formulation on Combination of Cecal Slurry, LPS and E. Coli Induced Systemic Inflammatory Response Syndrome (SIRS) in Sprague Dawley Rats - Mahendra, Kumar Trivedi; Alice, Branton; Dahryn, Trivedi; Snehasis, Jana (Journal of Current Scientific Research, 2021)
Sepsis is a systemic inflammatory response to a confirmed or suspected infection. The transition from sepsis to septic shock causes high rate of mortality. The aim of this experiment was to evaluate the anti-inflammatory potential of the Biofield Energy Treated (Blessed) Proprietary Test Formulation and Biofield Energy Healing (Blessing) Treatment per se to Sprague Dawley rats on Cecal Slurry, LPS, and E. coli-induced systemic inflammatory response syndrome (SIRS) model. In this experiment, various proinflammatory cytokines such as tumor necrosis factor-α (TNF-α), interleukin-1β (IL-1β), IL-6, IL-10, IL-12, 1L-17, and interferon-γ (IFN-γ) were analysed using ELISA. A test formulation was formulated including minerals (magnesium, zinc, calcium, selenium, and iron), vitamins (ascorbic acid, pyridoxine HCl, vitamin E, cyanocobalamin, and cholecalciferol), Panax ginseng extract, β-carotene, and cannabidiol isolate. The constituents of the test formulation were divided into two parts; one section was defined as the untreated test formulation, while the other portion of the test formulation and three group of animals received Biofield Energy Healing Treatment remotely for about 3 minutes by a renowned Biofield Energy Healer Mr. Mahendra Kumar Trivedi. The level of TNF-α was significantly reduced by 40.50%, 85.36% (p≤0.01), 50.66% (p≤0.01), 87.38% (p≤0.01), and 58.63% (p≤0.01) in G5 (Cecal Slurry, LPS, and E. coli + Biofield Energy Treated test formulation), G6 (Cecal Slurry, LPS, and E. coli + Biofield Energy Treatment per se to animals from day -15), G7 (Cecal Slurry, LPS, and E. coli + Biofield Energy Treated test formulation from day -15), G8 (Cecal Slurry, LPS, and E. coli + Biofield Energy Treatment per se + Biofield Energy Treated test formulation from day -15), and G9 (Cecal Slurry, LPS, and E. coli + Biofield Energy Treatment per se animals + untreated test formulation) groups, respectively as compared to the disease control (G2) group. Additionally, the level of IL-1β was decreased by 17.04%, 15.56%, and 12.59% in G6, G8, and G9 groups, respectively as compared to the untreated test formulation (G4) group. The level of IL-6 was significantly (p≤0.001) reduced by 36.18%, 50.24%, 43.25%, 52.69%, and 38.23% in the G5, G6, G7, G8, and G9 groups, respectively as compared to the G2 group. The level of IL-10 was altered by 70.53%, 49.25%, 60.18%, 41.54%, and 58.89% in G5, G6, G7, G8, and G9 groups, respectively as compared to the G2 group. Moreover, the level of IL-12 was decreased by 30.24%, 31.67%, 29.82%, 45.77%, and 50.54% in the G5, G6, G7, G8, and G9 groups, respectively as compared to the G2. The level of IL-17 was reduced by 48.75%, 59.61%, 59.28%, 62.49%, and 58.65% in the G5, G6, G7, G8, and G9 groups, respectively as compared to the G2. IFN-γ expression was reduced by 49.56%, 24.09%, 23.7%, 56.98%, and 44.94% in G5, G6, G7, G8, and G9 groups, respectively than G2. Overall, the data suggested anti-inflammatory potentials of the Biofield Energy Treated test formulation and Biofield Energy Treatment per se along with preventive measure on the animal with respect to various inflammatory conditions that might be beneficial various types of systemic inflammatory disorders specially sepsis, trauma, septic shock or any types of injuries. Therefore, the results showed the significant slowdown the inflammation-related disease progression and its complications in preventive treatment groups viz. G6, G7, G8, and G9.
Keywords: SIRS; Inflammatory cytokines; Biofield Treatment; The Trivedi Effect®; ELISA